Strategi Promosi Dalam Menarik Nasabah Tabungan Haji Di Bank Syariah Indonesia Kantor Cabang Sudirman Palembang - Karina Febrianti; Hasril Atieq Pohan (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to determine and analyze the promotional strategies implemented by Bank Syariah Indonesia (BSI) Sudirman Branch Office, Palembang, to attract Hajj Savings customers. Promotion is an important element in the marketing mix that serves to communicate products, increase public understanding, and encourage interest in becoming customers. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation of the bank and potential customers. The results show that BSI's promotional strategies include the use of digital media such as Instagram, Facebook, YouTube, and the BSI Mobile application; conventional media in the form of brochures, banners, and billboards; personal promotion through direct education by Customer Service and Tellers; and public relations activities through religious events and outreach in the Muslim community. These promotional strategies have proven effective in increasing awareness and interest of potential customers, although there are still obstacles in the form of a lack of detailed information regarding the mechanisms and benefits of Hajj Savings compared to other savings. This study recommends that BSI further strengthen promotional content that is educational, informative, and interactive in order to increase appeal and expand the reach of potential customers in the future.